Monitoring Dan Keamanan Smarthome Berbasis Internet Of Things (Iot) - Yudistira, Agung (Electrical Network Systems and Sources, 2025)
This study aims to design a home security system based on the Internet of Things (IoT) that can be operated via a smartphone application as a solution to security issues in Pontianak and West Kalimantan. Security threats such as burglary and fire are significant in this region, with 1,149 burglary cases reported in Pontianak and 3,470 cases in West Kalimantan in 2020. Additionally, there were 473 fire incidents between 2010 and 2015, primarily caused by electrical short circuits. The proposed system utilizes the Telegram application as a two-way communication medium, equipped with a flame sensor for fire detection and an MQ-2 sensor for gas leak detection. When these sensors detect a threat, the system responds by activating a water pump to extinguish the fire and a buzzer as an emergency alarm. The system can provide real-time notifications to users via Telegram, enabling a quick response to security threats. The findings indicate that this IoT-based security system not only provides effective notifications but also enhances control and convenience for homeowners, especially when they are away from home. It is hoped that this system can improve security and comfort for residents by allowing them to manage their homes more effectively